2021
DOI: 10.3390/md20010023
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet and Antithrombotic Effects of Isaridin E Isolated from the Marine-Derived Fungus via Downregulating the PI3K/Akt Signaling Pathway

Abstract: Isaridin E, a cyclodepsipeptide isolated from the marine-derived fungus Amphichorda felina (syn. Beauveria felina) SYSU-MS7908, has been demonstrated to possess anti-inflammatory and insecticidal activities. Here, we first found that isaridin E concentration-dependently inhibited ADP-induced platelet aggregation, activation, and secretion in vitro, but did not affect collagen- or thrombin-induced platelet aggregation. Furthermore, isaridin E dose-dependently reduced thrombosis formation in an FeCl3-induced mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The cyclodepsipeptides, scopularides A and B displayed potent larvicidal activity against mosquito ( Culex pipiens ) larvae, 277 alkaloids epi -aszonalenin A and aszonalenin were shown to inhibit angiogenesis by inhibition of inflammation and apoptosis 278 and cyclodepsipeptide isaridin E was shown to downregulate the PI3K/Akt signalling pathway and thus possesses antiplatelet and antithrombotic effects. 279 The alkaloid meleagrin had a protective effect in mice against pulmonary fibrosis induced by bleomycin 280 and epidithiodiketopiperazine N -methylpretrichodermamide B displayed potent inhibition of P-glycoprotein and was able to resensitise drug resistant cells to docetaxel. 281 Indolyl alkaloid oxaline and anthraquinone isorhodoptilometrin exerted weak anti-neuroinflammatory effects on murine cell lines 282 and the polyketide citrinin exhibited weak anti-parasitic effects against Trichomonas vaginalis .…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclodepsipeptides, scopularides A and B displayed potent larvicidal activity against mosquito ( Culex pipiens ) larvae, 277 alkaloids epi -aszonalenin A and aszonalenin were shown to inhibit angiogenesis by inhibition of inflammation and apoptosis 278 and cyclodepsipeptide isaridin E was shown to downregulate the PI3K/Akt signalling pathway and thus possesses antiplatelet and antithrombotic effects. 279 The alkaloid meleagrin had a protective effect in mice against pulmonary fibrosis induced by bleomycin 280 and epidithiodiketopiperazine N -methylpretrichodermamide B displayed potent inhibition of P-glycoprotein and was able to resensitise drug resistant cells to docetaxel. 281 Indolyl alkaloid oxaline and anthraquinone isorhodoptilometrin exerted weak anti-neuroinflammatory effects on murine cell lines 282 and the polyketide citrinin exhibited weak anti-parasitic effects against Trichomonas vaginalis .…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…272 Synthesis of the polyketide penicyclone A was accomplished in ten steps using a double Grignard reaction, 273 synthesis of raistrickindole A was achieved via two approaches to the diketopiperaine subunit, 274 a divergent strategy was employed in the synthesis of polyketides heterocornol A and B 275 and an Ir(III)-catalysed alkylation of acetophenone in aqueous medium was utilised in the total synthesis of cytosporones A and C. 276 The cyclodepsipeptides, scopularides A and B displayed potent larvicidal activity against mosquito (Culex pipiens) larvae, 277 alkaloids epi-aszonalenin A and aszonalenin were shown to inhibit angiogenesis by inhibition of inammation and apoptosis 278 and cyclodepsipeptide isaridin E was shown to downregulate the PI3K/Akt signalling pathway and thus possesses antiplatelet and antithrombotic effects. 279 The alkaloid meleagrin had a protective effect in mice against pulmonary brosis induced by bleomycin 280 and epidithiodiketopiperazine N-methylpretrichodermamide B displayed potent inhibition of P-glycoprotein and was able to resensitise drug resistant cells to docetaxel. 281 Indolyl alkaloid oxaline and anthraquinone isorhodoptilometrin exerted weak anti-neuroinammatory effects on murine cell lines 282 and the polyketide citrinin exhibited weak anti-parasitic effects against Trichomonas vaginalis.…”
Section: Cyanobacteriamentioning
confidence: 99%
“…However, it does not have any effect against thrombin- or collagen-induced platelet aggregation. Isaridin E also showed an antithrombotic effect without increasing bleeding time in a dose-dependent manner against the FeCl 3 -induced carotid mouse model [ 84 ]. F-fucoidan (FD) is a polysaccharide compound derived from the brown alga Laminaria japonica that also shows an antithrombotic effect through shortening the blood lysis time, H2O2 expression stimulation, and H2O2 released after induction of PGI2 production and might be effective in CVDs’ patients [ 103 ].…”
Section: Role Of Marine Drugs In Cvds Managementmentioning
confidence: 99%
“…Platelet hyperactivity occurring during sepsis causes disruption or dysfunction of the endothelium, leading to intravascular coagulation, which is the critical stage of multiple organ failure [ 12 ]. Our previous investigation revealed that isaridin E (ISE), a cyclodepsipeptide derived from the marine fungus Amphichorda felina SYSU-MS7908 sourced from the South China Sea, displayed antiplatelet and antithrombotic effects in both in vitro and in vivo thrombosis formation models induced by adenosine diphosphate (ADP) and FeCl 3 , respectively [ 13 ]. Notably, we observed that the bleeding risk of ISE in vivo was much lower compared to clopidogrel, and ISE did not exhibit cytotoxicity to mouse platelets at doses below 400 μM [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous investigation revealed that isaridin E (ISE), a cyclodepsipeptide derived from the marine fungus Amphichorda felina SYSU-MS7908 sourced from the South China Sea, displayed antiplatelet and antithrombotic effects in both in vitro and in vivo thrombosis formation models induced by adenosine diphosphate (ADP) and FeCl 3 , respectively [ 13 ]. Notably, we observed that the bleeding risk of ISE in vivo was much lower compared to clopidogrel, and ISE did not exhibit cytotoxicity to mouse platelets at doses below 400 μM [ 13 ]. These findings motivated us to further explore its efficacy in a thrombotic disease animal model, specifically sepsis, wherein platelet hyperactivity is critical to its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%